PENERAPAN METODE PROBLEM SOLVING LEARNING (PSL) DENGAN MEDIA BENDA KONKRET TENTANG BANGUN RUANG DALAM PENINGKATAN PEMBELAJARAN MATEMATIKA SISWA KELAS V SDN 7 KUTOSARI TAHUN AJARAN 2015/2016 - Waryanto, Slamet (KALAM CENDEKIA PGSD KEBUMEN, 2016)
Abstract: The Application of Problem Solving Learning (PSL) Model Using Concrete Media in Improving Mathematics Learning about Geometry for the Fifth Grade Students of SD Negeri 7 Kutosari in the Academic Year of 2015/2016. The objectives of this research to improve Mathematics learning through the application of PSL. This research is a collaborative Classroom Action Research (CAR) conducted within three cycles. Each cycle consisted of planning, action, observation, and reflection. Subjects of the research were teachers and students of the fifth grade of SD Negeri 7 Kutosari in the academic year of 2015/2016. The conclusion of this research is the application of PSL using concrete media can improve Mathematics learning for the fifth grade of SD Negeri 7 Kutosari in the academic year of 2015/2016.Keywords: Problem Solving Learning (PSL) method, concrete media, Mathematics learning Abstrak: Penerapan Metode Problem Solving Learning (PSL) dengan media benda konkret tentang Bangun Ruang dalam Peningkatan Pembelajaran Matematika Siswa Kelas V SD Negeri 7 Kutosari Tahun Ajaran 2015/2016. Tujuan penelitian ini untuk meningkatkan pembelajaran Matematika. Penelitian Tindakan Kelas (PTK) kolaboratif ini dilaksanakan dalam 3 siklus, yang terdiri dari perencanaan, pelaksanaan, observasi, dan refleksi. Subjek penelitian adalah guru dan siswa kelas V SDN 7 Kutosari tahun ajaran 2015/2016. Kesimpulan penelitian ini adalah penerapan metode PSL dengan media benda konkret dapat meningkatkan pembelajaran Matematika siswa kelas V SDN 7 Kutosari Tahun Ajaran 2015/2016.Kata kunci: metode Problem Solving Learning (PSL), media konkret, pembelajaran Matematika